2014
DOI: 10.1590/s0104-59702014000300010
|View full text |Cite
|
Sign up to set email alerts
|

The Kraken: when myth encounters science

Abstract: Hundreds of years ago, sailors were terrified by the Kraken, a dreadful sea monster capable of sinking ships and with a taste for human flesh. Today we know the legends of this monster were based on sightings of giant squids. This animal belongs to the genus Architeuthis and was the subject of many scientific studies. Despite its enormous size (up to 18m), the giant squid is astoundingly elusive and much of its biology remains unknown. Thus shrouded in mystery, Architeuthis is almost a mythological creature an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Cephalopods have long haunted the human imagination as monsters, inspiring mythology dating back to ancient Greek culture (e.g., the Hydra from the labors of Hercules, see Cousteau and Diolé , 1973 , p. 72–73, 75; the Gordon Medusa in Wilk, 2000 ), to legends of sea monsters in Nordic culture and among sailors throughout the middle ages ( Salvador and Tomotani, 2014 ), to the science fiction of the modern world (e.g., Sphere: Crichton, 1988 ; 20,000 Leagues Under the Sea: Verne, 1988 ), where they – or creatures strongly resembling them – often lurk in outer space as alien creatures from other worlds (as in the motion pictures Arrival 1 and Life 2 , to mention some). And while they were once reviled as “stupid” by Aristotle (1910) , and dangerous, as in Toilers of the Sea ( Hugo, 2002 ), this unique molluscan taxon has now come to be admired by both scientists, artists and the general public alike ( Nakajima et al, 2018 ).…”
Section: General Introductionmentioning
confidence: 99%
“…Cephalopods have long haunted the human imagination as monsters, inspiring mythology dating back to ancient Greek culture (e.g., the Hydra from the labors of Hercules, see Cousteau and Diolé , 1973 , p. 72–73, 75; the Gordon Medusa in Wilk, 2000 ), to legends of sea monsters in Nordic culture and among sailors throughout the middle ages ( Salvador and Tomotani, 2014 ), to the science fiction of the modern world (e.g., Sphere: Crichton, 1988 ; 20,000 Leagues Under the Sea: Verne, 1988 ), where they – or creatures strongly resembling them – often lurk in outer space as alien creatures from other worlds (as in the motion pictures Arrival 1 and Life 2 , to mention some). And while they were once reviled as “stupid” by Aristotle (1910) , and dangerous, as in Toilers of the Sea ( Hugo, 2002 ), this unique molluscan taxon has now come to be admired by both scientists, artists and the general public alike ( Nakajima et al, 2018 ).…”
Section: General Introductionmentioning
confidence: 99%
“…Others have suggested that the hafgufa was inspired by giant squid, due to confusion with the kraken, a mythical sea creature commonly described as a colossal squid or octopus. The discovery of intact specimens of giant squid from the 1870s makes this idea seem plausible (Salvador & Tomotani, 2014) but it is incorrect, and the error arises partly from a confusion between the kraken and hafgufa traditions. In 1741 the Norwegian‐Danish missionary, Hans Egede (1818, p. 87) stated that the kraken was the same creature known by the Icelanders as the hafgufa.…”
Section: Discussionmentioning
confidence: 99%
“…In 1741 the Norwegian‐Danish missionary, Hans Egede (1818, p. 87) stated that the kraken was the same creature known by the Icelanders as the hafgufa. This in turn led other scholars (e.g., Salvador & Tomotani, 2014, p. 972) to believe that the kraken appears in medieval texts. The kraken, however, is a modern sea monster, first appearing in the written record only in the early 1700s, and only coming to popular attention later that century.…”
Section: Discussionmentioning
confidence: 99%
“…Prominent among the mythical beasts is the Kraken, a giant octopus, of Norse mythology. The Kraken was an octopus of a size capable of devouring an entire ship with a taste for human flesh and its actual existence was accepted by Nordic naturalists up to and including Linnaeus in the late 18th century (e.g., Salvador & Tomotani 2014). Thus, the use of a giant octopus as a monster to be battled by the protagonist in Victor Hugo's 1866 novel, "Les Travailleurs de la Mer" (Toilers of the Sea), was not an original invention.…”
Section: A Vérany Cephalopod As An Archetypal Beast By Victor Hugomentioning
confidence: 99%